Study habits and academic performance in foreign language students - Reyna Alcántara, Ana de los Santos (2022)
This review article analyzes the digital competencies of teachers and their implication on teacher performance in Latin America in the face of the remote education modality due to the COVID-19 pandemic. The qualitative methodology used contemplates a documentary research design, resorting to the systematic review of different national and international bibliographic sources, such as normative documents, reports, scientific articles, books and organizational websites. The scientific articles reviewed are indexed in reliable databases such as Web of Science (ESCI), Scielo, Latindex. Among the main results we have that in the peruvian context about 60% of teachers have difficulties in the management of digital competencies, affecting a basic level in the creation and design of educational resources with ICT intermediation. It is concluded that teachers have difficulties in the development and application of digital competencies, which leads to poor performance in the current requirement to provide educational services remotely, needing to be trained and updated in these skills to improve the quality of education.